2017
DOI: 10.17265/2161-623x/2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Using Social-Networking Sites in Learning English Language and Students’ Self-Efficacy

Abstract: This paper aims to explore the academic students' purposes for using social-networking sites (SNSs) to enhance self-efficacy (SE) of learning English language. The SE is the appropriate theory that explains effectiveness of using SNSs on academic students' beliefs and performance positively. This study involves 286 participants from Umm AL-Qura University (UQU) in Mecca to answer a questionnaire. The results of the study show that there is no significant difference between male and female groups in familiarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…SNSs have recently received researchers' attention on how they can be integrated into the learning process. With regard to the use of SNSs in learning, some researchers, such as Arnold and Paulus (2020) and DeAndrea et al (2011), have observed that people can employ them to strengthen social interactions and foster communications through sharing knowledge in their group (as cited in Almarwaey, 2017). Other researchers have concentrated on using SNSs to improve the students' motivation in learning English.…”
Section: Social Networking Sites and English Language Learningmentioning
confidence: 99%
“…SNSs have recently received researchers' attention on how they can be integrated into the learning process. With regard to the use of SNSs in learning, some researchers, such as Arnold and Paulus (2020) and DeAndrea et al (2011), have observed that people can employ them to strengthen social interactions and foster communications through sharing knowledge in their group (as cited in Almarwaey, 2017). Other researchers have concentrated on using SNSs to improve the students' motivation in learning English.…”
Section: Social Networking Sites and English Language Learningmentioning
confidence: 99%
“…Using Social-Networking Sites in Learning English Language and Students' Self-Efficacy is another study done by Almarwaey (2017) where he aimed to explore the academic purposes of 286 students from Umm AL-Qura University for using social-networking sites (SNSs) to enhance self-efficacy (SE) of learning English language .The findings depicted that SNSs can be online learning platform to the students and teachers communicate with each other in English sharing educational materials and resources. Moreover, this platform can posit an enjoyable and useful learning environment through sharing, communication and socialisation.…”
Section: Literature Reviewmentioning
confidence: 99%